(3cJGH eYQaI eSGMI GdCTcGd GdHSjWI hGdcQjIs - ((3Hfj ehSi (B( (3eMeO hGdMSf hCMeOs
(3ChdgG (B:s
(3GdWhd Chd GdGbOGQ GdJi JMO GdCTcGd hgh eG GeJO Ydi GSJbGeI ai GdLgJjf LejYkG s
(3BNQgG (B:s
(3agh KhGH hYdi gPG GdbjGS GeQ GdeSGFd hced eG hUafG ai cJGHfG aEfg ef Yed eGfdGhS ceG eQ PcQg Je GdcJGH s
(3Vef eLehY , JQJjHgG (B: (3GdcJGH GdKGdK YTQs
(3GdfSNI HgG MhGTs
(3GfXQg eY GdeNWhW Qbe (B66 (3ef faS GdHYKIs
(3HgG fXGe GdJYbjHIs
(3GdJhKjbGJ GdeQLYjI (B:s
(3cTa GdXfhf dMGLi NdjaI(B: (3L (B2 - (3U (B1458s
(3eUOQ GbJfGA GdCUd (B:s
Keywords: (3GdQjGVjGJs